2011
DOI: 10.1155/2011/636170
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of 2,3‐Butanediol Production by Klebsiella oxytoca PTCC 1402

Abstract: Optimal operating parameters of 2,3-Butanediol production using Klebsiella oxytoca under submerged culture conditions are determined by using Taguchi method. The effect of different factors including medium composition, pH, temperature, mixing intensity, and inoculum size on 2,3-butanediol production was analyzed using the Taguchi method in three levels. Based on these analyses the optimum concentrations of glucose, acetic acid, and succinic acid were found to be 6, 0.5, and 1.0 (% w/v), respectively. Furtherm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 19 publications
1
9
0
1
Order By: Relevance
“…In 2, 3‐BDO fermentation, acetate has been identified as not only an inhibitor but also a substrate to K. oxytoca . Acetate might be an inducer for 2, 3‐BDO pathway genes, and in its ionized form induces acetolactate synthase formation and thereby enhances the catalysis of pyruvate to 2, 3‐BDO . This could explain why 2, 3‐BDO yield in medium with acetic acid addition is higher.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2, 3‐BDO fermentation, acetate has been identified as not only an inhibitor but also a substrate to K. oxytoca . Acetate might be an inducer for 2, 3‐BDO pathway genes, and in its ionized form induces acetolactate synthase formation and thereby enhances the catalysis of pyruvate to 2, 3‐BDO . This could explain why 2, 3‐BDO yield in medium with acetic acid addition is higher.…”
Section: Discussionmentioning
confidence: 99%
“…Acetate might be an inducer for 2, 3-BDO pathway genes, and in its ionized form induces acetolactate synthase formation and thereby enhances the catalysis of pyruvate to 2, 3-BDO. 20 -22 This could explain why 2, 3-BDO yield in medium with acetic acid addition is higher. A decrease in 2, 3-BDO yield was observed when acetic acid concentration reached a certain value, which is decided by the amounts of furfural, HMF and acetic acid in medium.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have previously reported that yeast extract, ammonium acetate, ammonium sulfate, glycerol, and tryptone, as well as temperature and inoculum size influence microbial 2,3-BD production [16][17][18][19][20]. Some of these studies concluded that using high concentrations of expensive yeast extract (up 60 g/L) was crucial for optimal 2,3-BD production.…”
Section: Experimental Design and Data Analysismentioning
confidence: 99%
“…BP:B oron phosphate was synthesized by using an organic precursor,t ri-iso-propylborate (B(iPrO) 3 ). B(iPrO) 3 was mixed with orthophosphoric acid (85 %). The B/P molar ratio was equal to 1.…”
Section: Catalyst Preparationmentioning
confidence: 99%
“…Its ester derivatives are precursors of polyurethane and can be applied in cosmetic, pharmaceutical, and other industries. [1,3] But the most important applications are connected with BDO dehydration into butan-2-one (methyl ethyl ketone,M EK), 3-buten-2-ol( 3B2OL), and 1,3-butadiene (BD). [1b, 4-6] MEK is aw idely used organic solvent as well as ap recursor for MEK peroxide.…”
Section: Introductionmentioning
confidence: 99%